The Effect of Two Stay Two Stray Cooperative Model on Students' Mathematical Comprehension Ability in Elementary Schools - Andes Safarandes Asmara; Inda Yulistiawati; Tarpan Suparman - (Jurnal Sekolah Dasar, 2020)
This research aims to determine the influence of the Koopertatif Type Two Stay Two Stray (TSTS) model on the mathematical understanding capabilities of elementary school students. This research was conducted at SDN Warung Bambu II East Karawang Sub-District of Karawang Regency. This research is a type of quantitative research. In this study, a sample of 30 people using Simple Random Sampling technique and divided into two groups, namely the experiment group and the control group. The research instruments used are multiple choice. The test is used to measure mathematical comprehension capabilities. The data analysis technique used is statistical calculation. The results of the multiple choice question test validity test in mathematics subjects were obtained 20 items of instruments that were declared valid from 30 instruments tested. The result of the rehab was a value of 0.97. Hypothetical test results, with a degree of signifiability between the Type Two Stay Two Stray cooperative model and the results of mathematical understanding capabilities. It is obtained thitung = 0.514 > ttabel 4,409) with sig = 0.000 > 0.05 and n = 30 indicates that the hypothesis is rejected. From the results of this study can be concluded that there is a perngaruh mathematical understanding capability that uses the Cooperative Model Type Two Stay Two Stray (TSTS).